Asymmetry of metacarpal skeleton : analyses of second, third and fourth metacarpal bone dimensions - Kušec, Vesna (Array, 1990)
Asymmetry between metacarpal bones of the left and right hand was investigated in a sample of 968 subjects (419 males and 549 females, aged between 19 and 86) living on the island of Pag, Croatia, exposed to everyday hard physical activity. Morphometry was performed on hand-wrist radiographs of both hands on the second, third and fourth metacarpal bones. Data ("bone length" - L, "total diaphysis width" - T, and "medullary canal width" - M) were submitted to several statistical procedures. Dimensions of metacarpal bones are in general greater on the right hand in both sexes, while the asymmetry between the metacarpal dimensions is more pronounced in males than in females. The greatest degree of asymmetry of morphometric variables exists for the "total diaphysis width" (T), and of metacarpal bones for the fourth one in both sexes too